2016
DOI: 10.2350/15-08-1695-cr.1
|View full text |Cite
|
Sign up to set email alerts
|

Is Identification of Lupus Erythematosus Cells Still Useful? A Case Report

Abstract: A 13-year-old girl presented with significant weight loss, depression, anemia, and neutropenia. The preliminary diagnosis was anorexia nervosa combined with depression. Due to peripheral cytopenia, a bone marrow biopsy was performed to rule out leukemia. Lupus erythematosus (LE) cells were found in the bone marrow aspirate, which prompted autoantibody testing, although clinically it was not suspected the patient had systemic lupus erythematosus (SLE). Further testing demonstrated very high levels of antinuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 10 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…Review of the 15 pediatric SLE bone marrow aspirates revealed LE cells in only 1 patient (P1), the index case in the previous case report. 14 However, hematoxylin bodies were present in the bone marrow aspirates of 8 patients (P1–P8) (8/15, 53%). As shown in Figure 1(A) and (B), hematoxylin bodies in the bone marrow aspirates with Wright–Giemsa stain appear as magenta to purple, dense, homogeneous round or oval bodies with a size of 0.5 to 1.5 times that of neutrophils.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Review of the 15 pediatric SLE bone marrow aspirates revealed LE cells in only 1 patient (P1), the index case in the previous case report. 14 However, hematoxylin bodies were present in the bone marrow aspirates of 8 patients (P1–P8) (8/15, 53%). As shown in Figure 1(A) and (B), hematoxylin bodies in the bone marrow aspirates with Wright–Giemsa stain appear as magenta to purple, dense, homogeneous round or oval bodies with a size of 0.5 to 1.5 times that of neutrophils.…”
Section: Resultsmentioning
confidence: 95%
“…However, the finding of LE cells in bone marrow and body fluids in previous reports has prompted the testing of autoantibodies and resulted in the diagnosis of unexpected SLE. 813 In our recent case report, 14 LE cells were identified in the bone marrow aspirate of an adolescent girl who was thought to have anorexia nervosa and depression. The bone marrow biopsy was performed to rule out leukemia, suspected due to anemia and neutropenia.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…2 Hematoxylin bodies are engulfed by neutrophils, resulting in the formation of LE cells. 2,3 In cytological preparations, LE cells must be distinguished from "tart cells" or "pseudo-LE cells," which result from the phagocytosis of nuclear debris by macrophages rather than neutrophils and are generally observed in effusion fluid. 3 The phagocytosed debris within a tart cell is smaller and has a nonhomogeneous (clumped) appearance in contrast to the smooth, homogeneous nature of hematoxylin bodies in true LE cells.…”
Section: Introductionmentioning
confidence: 99%